PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 37 GAJAH SAKTI KECAMATAN MANDAU KABUPATEN BENGKALIS - Sri Maharani; Lazim N Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : For a long time, the study process still embrace conventional study model, that is study process which is centre on learn so that process and study of self supporting in learning will cannot be seen. Conventional study assumes that teacher as a source learns which assumed completely knows. This matter is strengthened by observation result which has been done by researcher before doing research, and in fact, Lessons moment started by many students conversing by themselves and looked to be once feel be fed up with method done by eye teacher of Science. This matter is anticipated will influence activity learn student in class. Studies from the problem above, generally the research are about: The Process of Study Planning Inquiry Method on Science for grade V in SD Negeri 37 Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis. The execution of process inquiry method to increase the result of students in studying Science of grade V SD Negeri 37 Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis. Assessment process of inquiry method to increase the study result of student in grade V SD Negeri 37 Gajah Sakti Kecamamatan Mandau Kabupaten Bengkalis. This research was done in Duri city, in SD Negeri 37 Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis. This is a research of Class Research. The steps research was a cycle such as Planning, Implementation, Observation, and Reflection. The techniques used for collecting data were Observation and Measurement of result of study. Based on the result of research conclude that the used of inquiry method can increase the result of student in studying. The result of research shows that inquiry method can increase the result study of the student especially in Science. This is as a fact that the average mark of student 31,81 can increase into 72,95 in cycle I and for the cycle II its increase to 77,27.Key Words: Inquiry Method, Science study result